INCORPORATING MALE AND FEMALE PERCEPTIONS ON GENDER VIEWS OF SELECT NORTHERN CEBUANOS IN DEVELOPING ICT-BASED INFORMATION EDUCATION AND COMMUNICATION DRIVE ON GENDER AWARENESS - Ungui, Ruben M; Dato-on, Rowena P; Godinez, Marlou C; Ybañez, Adrian P (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Much has been said about gender equality which has become the topic of the modern world, especially women empowerment. While this is the talk of the century little is done in the dissemination of research outputs to correct the gray areas of gender equality. In particular, this paper mainstreams the gender equality perspective of Cebuano men and women accompanied by views on a variety of topics related to gender equality to develop an ICT-based information education and communication drive that helps promote gender equality. The researchers employed a gender audit survey to know the perceptions of both male and female on gender views such as household division of labor, gender-related and health- related practices, views about sex, and men and women’s views on education and work and family decision- making. Significant results were found among male and female respondents such that their perceptions on household division of labor were congruent. However, they vary on different aspects in gender and health relates practices, views on sex, views on education and work and family decision making. A Kruskal-Wallis Test was employed and it reflected in the results that there is a significant relationship between gender and the perceptions at .295 given the 95% confidence level. The male and female respondents may have different gender views. However, they both hold the same aspiration: easy access and acceptable information on gender equality via ICT. Therefore, the development of an ICT-based information education and communication drive would be very effective in delivering reliable information on gender equality.